Economics of Tourism and Sustainable Development Libya study case (Comprehensive Journal of Science, 2025)
Tourism is a global force for Economic and sustainable development. Tourism development brings with it a mix of benefits and costs and the growing field of tourism economics is making an important contribution to tourism policy, planning and business practices. First, questions can be raised about the validity of focusing measures of successes solely on the uncritical use of GNP data. Second, environmental accounting techniques seek to include a wide range of considerations when considering the cost and benefits of particular projects. When subjected to environmental secrutity, the tourism sector can display examples of previously unaccounted overall benefits as well as costs. Additionally, as well as being the preparatory of negative environmental pollution. Tourism is now one of the world’s largest industries and one of its fastest growing economic sectors. For many countries tourism is seen as a main instrument for sustainable development, as it stimulates new economic activities. Tourism may have a positive economic impact on the balance of payments, on employment, on gross income and production, but it may also have negative effects, particularly on the environment. Unplanned and uncontrolled tourism growth can result in such a deterioration of the environment that tourist growth can be compromised. The environment, being the major source of tourist product, should therefore be protected in order to have further growth of tourism and economic development in the future. Although much of the environmental debate focuses on the detrimental effects of economic development, there are also benefits which can be noted. The existence of tourism in remote rural areas can make difference between local shops remaining profitable, and therefore open, or not. Similarly the income and interest derived from tourists help to preserve heritage sites, contributing to restoration and upkeep. National parks and forest provide not only facilitates for tourism.  The paper found that tourism sector needs more investment beside substantial reforms in deferent areas, in regard of protect the environments and fight the pollution. Sustainable implies permanence, so sustainable tourism includes optimum use of resources, including biological diversity; minimizing of ecological, cultural and social impact; and maximization of benefits for conservation and local communities. It also refers to the management that needed to achieve this.  The paper provides a theoretical framework for sustainable tourism. It comprises two parts. The first part presents general views on tourism and sustainable economic development, and some opinions on the relationship between tourism and the sustainability. The second part concentrates on strategies and policy instruments
Keywords: tourism, sustainable, growth, deterioration, environment, heritage, preserve